Hubungan VO2Max dengan Resiko Cedera pada Pemain Voli Amatir di Klub Bola Voli Jakarta - Agustiyawan Agustiyawan; Rena Mailani; Fidyatul Nazhira; Ailsa Nahda Ahnafa Amsah; Aby Bima Kesuma (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: to identify the relationship between VO2Max and risk of injury among volleyball playersMethods: this study used a cross-sectional study on 26 male amateur volleyball players method with aged 15 – 18 years. VO2Max was recorded by cooper test and risk of injury was measured by Functional Movement Screen (FMS) Test.Results: the result obtained that there is relationship the VO2Max and risk of injuries (p = 0.001). A negative correlation was recorded between the VO2Max and risk of injuries (r = -0.723). Conclusion: The concluded that there is a relationship between VO2Max and risk of injury on amateur volley players with a negative correlation.